Estrategia adaptativa del leño Aspidosperma quebracho blanco - Graciela Moglia, Juana; López, Carlos Raúl (Instituto de Ecología, A.C., 2016)
In order to study if mechanical elements are involved in conduction, relationships between wood anatomical variables and functional relations were analyzed. For this purpose canonical correlation analysis was performed. Vessel area, diameter and length were selected as the dependant set to represent xylem conductivity, and fiber diameter, length and wall thickness as well as fiber percentage as the independent set, associated to mechanical elements, assuming that they are involved in conduction too. Results showed that both sets of variables were highly correlated showing the association between conduction and mechanical systems. Aspidosperma quebracho-blanco has specialized xylem to avoid water stress. Solitary vessels provide efficient water conduction, while tracheids and fiber-tracheids provide a subsidiary system responsible also of water movement. In this species xylem works as an interconnected network in which conductive and resistance systems are interrelated.